Comparative Proteomics and Phosphoproteomics Analysis Reveal the Possible Breed Difference in Yorkshire and Duroc Boar Spermatozoa - Xu, Yongjie; Han, Qiu; Ma, Chaofeng; Wang, Yaling; Zhang, Pengpeng; Li, Cencen; Cheng, Xiaofang; Xu, Haixia (Frontiers in Cell and Developmental Biology, 2021)
Sperm cells are of unique elongated structure and function, the development of which is tightly regulated by the existing proteins and the post-translational modifications (PTM) of these proteins. Based on the phylogenetic relationships of various swine breeds, Yorkshire boar is believed to be distinctly different from Duroc boar. The comprehensive differential proteomics and phosphoproteomics profilings were performed on spermatozoa from both Yorkshire and Duroc boars. By both peptide and PTM peptide quantification followed by statistical analyses, 167 differentially expressed proteins were identified from 1,745 proteins, and 283 differentially expressed phosphopeptides corresponding to 102 unique differentially phosphorylated proteins were measured from 1140 identified phosphopeptides derived from 363 phosphorylated proteins. The representative results were validated by Western blots. Pathway enrichment analyses revealed that majority of differential expression proteins and differential phosphorylation proteins were primarily concerned with spermatogenesis, male gamete generation, sperm motility, energy metabolism, cilium morphogenesis, axonemal dynein complex assembly, sperm-egg recognition, and capacitation. Remarkably, axonemal dynein complex assembly related proteins, such as SMCP, SUN5, ODF1, AKAP3 and AKAP4 that play a key regulatory role in the sperm physiological functions, were significantly higher in Duroc spermatozoa than that of Yorkshire. Furthermore, phosphorylation of sperm-specific proteins, such as CABYR, ROPN1, CALM1, PRKAR2A and PRKAR1A, participate in regulation of the boar sperm motility mainly through the cAMP/PKA signal pathway in different breeds, demonstrating that protein phosphorylation may be an important mechanism underlying the sperm diversity. Protein-protein interaction analysis revealed that the 14 overlapped proteins between differential expression proteins and differential phosphorylation proteins potentially played a key role in sperm development and motility of the flagellum, including the proteins ODF1, SMCP, AKAP4, FSIP2 and SUN5. Taken together, these physiologically and functionally differentially expressed proteins (DEPs) and differentially expressed phosphorylated proteins (DPPs) may constitute the proteomic backgrounds between the two different boar breeds. The validation will be performed to delineate the roles of these PTM proteins as modulators of Yorkshire and Duroc boar spermatozoa.